Iowa Birdline update, December 19, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email of the Iowa Birdline update for December 19, 1994. Highlights of the update include the first of the Christmas bird counts and the outstanding birds that were observed, including a Say's Phoebe, a Black-legged Kittiwake, a Bohemian Waxwing, an adult male White-winged Scoter, Surf Scoters, and three Long-tailed Ducks. Also of note were several species of Gulls, including an adult Lesser Black-backed Gull, a first winter Great Black-backed Gull, three first winter Thayer's Gulls, and four Glaucous Gulls. Also included is a typewritten update for the next week's report with sightings of Merlin, Brown Thrasher, and updates on previously seen birds. Epson - sheet feed/flatbed